Sosialisasi Strategi Umkm Dalam Meningkatkan Nilai Ekonomi Melalui Diversifikasi Pangan Lempuk Durian Di Anggut Bengkulu - Irwanto, Tito; Putra, Iswidana Utama; Wahyuni, Amalia; Wagini, Wagini; Gayatri, Ida Ayu Made Er Meytha (Universitas Dehasen Bengkulu, 2024)
MSMEs have a very important role to improve the economy of a country. With the existence of MSMEs, it is able to facilitate the government in pursuing economic growth. In Indonesia, the number of MSMEs continues to increase every year, people who have an interest in business and business will establish MSMEs that are able to increase economic growth in their area. Bengkulu is a province that has also experienced an increase in MSMEs, there is a lot of potential in Bengkulu province so that it can be used as a business or business activity by the community, one of which is the management of durian fruit into durian lempuk in the Angut area of Bengkulu. In improving the efforts that have been made by the community, it is also necessary for people who are creative and innovative in developing their business so that they are able to compete globally so that durian lempuk can become an icon as a typical food of the Bengkulu province. the purpose of this service is to socialize to the community and motivate them to continue to increase the potential of the region so that they are able to create quality and growing MSMEs.